Capital, Distribution, and the Aggregate Production Function - Harris, Donald J. (American Economic Review, 2016)
Recent results in capital theory concerning the reswitching of techniques of production have shaken the foundations of a neoclassical parable according to which the total quantity of output per man is supposed to be a function of the total quantity of capital per man-the Surrogate Production Function-which can be used to predict all behavior in the sense of the wage and profit rates that would prevail in different long-run equilibria or steady states.' The source of the difficulty, it would appear, lies in the fact that the neoclassical parable attempts, as it were, to kill two birds with one stone, namely 1) to provide a general representation (or surrogate) of realistic technologies involving production with heterogeneous commodities, and 2) to link the determination of the (listribution of income directly to the technology itself and to the relative size of factor endowments. It turns out that, in general, not only are realistic